Menyingkap Aspek Kecerdasan Profetik (Sebuah Telaah Ayat Manṭiqiyah) - Julhina, Julhina; Amir, Abdul Muiz (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2023)
This research aims to uncover the prophetic intelligence aspect through the interpretation of Surah Āli-'Imrān [3]:190-191 as part of the manṭiqiyah verses. This research implements the Ma'nā-cum-Maghzā interpretation through four stages of analysis: linguistic, grammatical analysis, intra- and intertextual analysis, micro and macro-historical analysis, and contextual analysis. These four analyses aim to reveal the historical and contextual significance messages of Surah Āli-'Imrān [3]:190-191. The research findings demonstrate that logic plays a vital role in unravelling the most profound messages in each Quranic verse. Linguistically, the phrase Ūlil Albāb encompasses human faculties that are logical and spiritual (contemplating and remembering Allah), thus it is inaccurate if the thinking process is deemed separated in the interpretation process of revelation texts. Historically, several cases from the Hadith narrations were discovered that illustrate how the Prophet responded to several similar questions but with different answers. This exhibits that the Prophet underwent a thinking process to tailor his answers to the context and the questioner. However, reasoning alone is insufficient without the spiritual intuition because thinking without spiritual discipline can yield value-free thoughts. This kind of contemplation was bequeathed by the Prophets which the author coins as the prophetic intelligence aspect. Based on these research findings, the significance messages of Surah Ali-'Imran [3]:190-191 assert that reason is not value-free; instead, it constitutes part of the revelation interpretation apparatus